Elastic properties of hydrate-bearing sandy sediment during CH4–CO2 replacement. (15th July 2015) - Wang, Xiao-Hui; Li, Feng-Guang; Xu, Yu-Xi; Sun, Chang-Yu; Pan, Heng; Liu, Bei; Yang, Lan-Ying; Chen, Guang-Jin; Li, Qing-Ping
Highlights: P-wave velocity was in-situ measured for CH4 –CO2 (gas or liquid) replacement experiments. P-wave velocity and amplitude both decrease with increase of replacement percent. The elastic moduli of hydrate-bearing sediment reduces during the replacement process. The fluctuation of bulk stiffness is low and the stiffness of hydrate-bearing sediments can be maintained. Abstract: CH4 –CO2 replacement method can not only recover methane from natural gas hydrate, but also implement CO2 geological sequestration. The effect of CH4 –CO2 replacement with gaseous or liquid CO2 from natural gas hydrates, and the stiffness evolution during the stages of CH4 hydrate formation, free methane gas release, gaseous or liquid CO2 flooding, and CH4 –CO2 replacement were experimentally investigated by in situ measuring the compressional wave velocity of hydrate-bearing sediments. The measured results showed that the P-wave velocity and amplitude of the hydrate-bearing sediments behave in the same way and decrease slightly because of the dissociation of CH4 hydrate when free CH4 gas was released and CO2 gas was injected. At the stage of CH4 –CO2 replacement, methane hydrate may be coated by newly-formed hydrate which prevents CH4 or CO2 molecules passing through. Both the P-wave velocity and the amplitude gradually decrease with the increase of replacement percentage owing to the different properties between CH4 hydrate and CO2 hydrate. The elastic modulus of hydrate-bearing sediments was found to decrease with the dissociation of CH4 hydrate and the formation of CO2 hydrate, indicating the CH4 –CO2 replacement may weaken the rigidity of the sediment skeleton. However, the fluctuation of bulk stiffness is at a low level and the stiffness of hydrate-bearing sediments can still be maintained.